2012
DOI: 10.1159/000339271
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Adrenergic Receptors, from Their Discovery and Characterization through Their Manipulation to Beneficial Clinical Application

Abstract: β-Adrenergic receptors (β-AR) are central to the overall regulation of cardiac function. From the first proposed receptor/transmitter concept to the latest clinical β-blocker trials β-AR have been shown to play an important role in cardiac disease and heart failure in particular. This study provides a historical perspective, reviews the latest discoveries and beliefs, and discusses the current clinical practices of β-AR and their modulation with their associated guanine-nucleotide regulatory protein/adenylylcy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 107 publications
0
87
0
2
Order By: Relevance
“…Propranolol previously was shown to act as an inverse agonist in the heart [11], and thus would be expected to reduce autophagosome formation rather than block it at a later stage of autophagy. Our findings showed that propranolol blocked hepatic autophagy in the absence of agonist, so it had its own intrinsic activity in addition to acting as a β-adrenergic antagonist against clenbuterol-induced hepatic autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propranolol previously was shown to act as an inverse agonist in the heart [11], and thus would be expected to reduce autophagosome formation rather than block it at a later stage of autophagy. Our findings showed that propranolol blocked hepatic autophagy in the absence of agonist, so it had its own intrinsic activity in addition to acting as a β-adrenergic antagonist against clenbuterol-induced hepatic autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, β-adrenergic receptor antagonists, known as “β-blockers” often are used to treat hypertension and ischemic heart disease [11]. Elucidation of the β-adrenergic receptor signalling mechanisms has deepened our understanding of many fundamental physiological and cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, after binding to β 2 -receptor, β 2 -agonists activated several sub-units of G protein family which consequently causes glucose-stimulated and hormone-stimulated insulin secretion 13,22 . When using at dosage of 10mg/kg and 100mg/kg consecutively in 30 days, clenbuterol induced a significant decline in glucose concentrations in mice 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Ons eigen onderzoek suggereert dat activatie van met name b-adrenoceptoren cognitieve controle kan verbeteren [6]. Hoewel dit een interessante en belangrijke bevinding is, ligt klinische toepassing van b-adrenoceptoragonisten bij verminderde zelfcontrole niet voor de hand, met name vanwege de perifere effecten en bijwerkingen van dergelijke agonisten op het autonome zenuwstelsel en het cardiovasculaire systeem [7].…”
Section: Noradrenalineunclassified